DAMPAK KREDIBILITAS PERUSAHAAN DAN PUBLIK FIGUR DALAM PERIKLANAN TERHADAP MINAT BELI YANG DIMEDIASI OLEH SIKAP KONSUMEN SERTA CITRA MEREK - Muhammad Aqsa; M Risal (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The characteristics of public figures in advertising are often the critical success factors in promoting or advertising a product. Recently other factor needs attention is the credibility of the company. The credibility of the company becomes a crucial point that is always problematized by customer. In fact, this credibility is basic of formation the long-term confidence that is proved to be a crucial point in the developing a business. For business growth it is important think for customer to make decision and in a long term it’s become a fundamental think for a customer trust. The purpose of this study was to identify the effects of corporate credibility and characteristics of public figures on advertising toward consumer attitudes and brand image and its impact on consumer purchases intention. The research method used is descriptive and verification. This study surveyed 200 respondents. Analysis using Lisrel 8.7. The results confirmed that the credibility of the company had a strong influence on consumer attitudes toward advertising, brand image and purchase intention while the  characteristics of public figures have a strong influence no attitudes toward advertising and brand image but to purchase intention it is weak. The findings indicated that the credibility of the company played an important role in as a stimulus consumer behavior, with in consumer attitudes toward advertising, enhance brand image and purchase intention, either beyond the role is as important as  characteristics of public figures as model in the advertisment.